Analyzing ChatGPT Impact on Student Productivity in Information Technology Program at Politeknik Negeri Tanah Laut - Hafizd, Khairul Anwar; Manalu, Mamed Rofendi; Arif, M Aidil (Universitas Budi Darma, 2025)
The rapid development of generative artificial intelligence, particularly ChatGPT, has transformed the way students complete academic tasks, especially in the field of Information Technology. Despite its widespread adoption, concerns remain regarding its impact on students’ productivity and learning quality. This study aims to analyze the effect of ChatGPT usage on the productivity of students in the Information Technology Study Program at Politeknik Negeri Tanah Laut. A quantitative research approach with a survey method was employed. Data were collected through a Likert-scale questionnaire distributed to active students who had used ChatGPT for academic purposes. The collected data were analyzed using validity and reliability tests, followed by simple linear regression analysis to examine the effect of ChatGPT usage on student productivity. The results indicate that ChatGPT usage has a positive and significant effect on student productivity. Productivity improvements are mainly observed in task efficiency and timely task completion. However, the quality of academic outputs remains highly dependent on students’ ability to critically evaluate, verify, and further develop the outputs generated by ChatGPT. These findings suggest that ChatGPT functions effectively as an academic assistant rather than a substitute for critical thinking and independent learning. This study concludes that ChatGPT can be utilized as a supportive academic tool to enhance student productivity when used appropriately and responsibly, supported by adequate AI literacy and academic supervision. The findings are expected to provide empirical insights for higher education institutions in formulating policies and guidelines for the ethical and productive use of ChatGPT in academic activities.